The Influence of Career Development and Workload on Turnover Intention with Job Satisfaction as a Mediator - Fitri Rezeki; Nasrun Baldah; Fachrurazi Fachrurazi; Preatmi Nurastuti; Yunita Ramadhani RDS (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
This research investigates the dynamics of Career Development, Job Satisfaction, Workload, and their impacts on Turnover Intention among employees. Through hypothesis testing and statistical analysis, significant insights into the relationships between these variables are uncovered. Firstly, Career Development is found to have a substantial positive influence on Turnover Intention, emphasizing the importance of providing avenues for career growth and advancement within organizations. Additionally, Job Satisfaction emerges as a critical factor, significantly mediating the relationship between Workload and Turnover Intention. The study also reveals a strong association between Job Satisfaction and Turnover Intention, underlining the pivotal role of employee contentment in mitigating turnover rates. These findings provide valuable guidance for organizations seeking to optimize their human resources management strategies, emphasizing the importance of fostering career development opportunities and prioritizing employee satisfaction to enhance overall retention efforts.